2017
DOI: 10.1080/17453674.2017.1405669
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bearing type on the outcome of total hip arthroplasty

Abstract: Background and purposeAlternative bearing surfaces such as ceramics and highly crosslinked polyethylene (HXLPE) were developed in order to further improve implant performance of total hip arthroplasties (THAs). Whether these alternative bearing surfaces result in increased longevity is subject to debate.Patients and methodsUsing the Dutch Arthroplasty Register (LROI), we identified all patients with a primary, non-metal-on-metal THA implanted in the Netherlands in the period 2007–2016 (n = 209,912). Cumulative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 18 publications
2
22
0
1
Order By: Relevance
“…1). This was similar to previous studies using LROI data [4,8,9,14]. Smoking status, BMI, and Charnley score were registered since 2014 in the LROI.…”
Section: Dutch Arthroplasty Registrysupporting
confidence: 90%
“…1). This was similar to previous studies using LROI data [4,8,9,14]. Smoking status, BMI, and Charnley score were registered since 2014 in the LROI.…”
Section: Dutch Arthroplasty Registrysupporting
confidence: 90%
“…To our knowledge, this is the first study utilizing NJR data that differentiated between XLPE and conventional PE when comparing different bearing combinations. Our analysis confirms a significant association between modern bearing surface combinations and THA survival, and corroborates previous analyses using data from the Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR) 7 and the Dutch Arthroplasty Register (LROI) 10 . However, registry data that do not stratify for PE modifications are used to inform policy 17 , 18 .…”
Section: Discussionsupporting
confidence: 88%
“…The LROI performed a similar analysis of THA survival with different bearings 10 . With MoP as the reference in a multivariate model, they also reported a reduction in the risk of revision in association with CMoXLPE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HXLPE was developed to reduce wear in conventional PE liners. Meanwhile, the incidence and severity of osteolysis secondary to wear would also be decreased [ 4 ]. Mutimer et al [ 5 ] reported that HXLPE had a lower revision rate compared with traditional PE with an average follow-up period of 5.5 years.…”
Section: Discussionmentioning
confidence: 99%